Three years post fire areas natural regeneration of peat swamp forest in Merang, Musi Banyuasin District, South Sumatera - Adi Kunarso; Tubagus Angga Anugrah Syahbana; Dony Rachmanadi (Jurnal GALAM, 2022)
This study examines natural regeneration of tropical peat swamp forest after fire. The study area is located in Merang Peat Swamp Forest (PSF) in Musi Banyuasin District. Merang PSF is situated over a large peat dome that stores huge amount of carbon. 23 sample plots were established in the area burned in 2015. The regeneration of understorey, seedlings, and saplings was recorded in each plot. Meanwhile, peat depth and its maturity were identified to determine the soil characteristic of study area. After 3 years of fire, the area already covers densely by understorey mainly pakis udang (Stenochlaena palustris), pakis tanah (Nephrolepis exaltata), and resam (Gleichenia linearis) with depth of root zone reach about 40 cm in some plots. The native peat swamp species showed minimal regeneration during third years after fire due to understorey covering and limited number of surviving trees. The natural regeneration of woody species was dominated by bangun-bangun (Melicope glabra) and sepongol (Evodia sambuciana) which were calculated about 371 saplings/ha and 200 saplings/ha respectively. Those all two species also founded in the seedlings stage. The peat depth varied from 0.32 m to 4.71 m with peat maturity is dominantly hemic in the subsurface. This regeneration information provides useful indications for restoration options, which could be done by assisted natural regeneration